PRESENCE AND INOCULUM DENSITY OF Phytophthora IN DIFFERENT COCONUT CULTIVARS IN DAVAO RESEARCH CENTER (DRC) - N.C.S.J. Bachiller (CORD, 2004)
Presence of Phytophthora palmivora was both obtained in the soil samples and organic debris layed in leaf axil of coconut. Block planted to CAMT x MRD hybrid had the highest number of Phytophthora propagules (2.0). This was followed by CAMT (1.4) and KINGD (1.1). Aromatic and Catigan Green Dwarf had the least Phytopthora propagules collected. Isolation of Phytophthora from the soil samples and organic debris from leaf axil was done thru dilution plate and baiting method respectively using six month old Malayan Red Dwarf (MRD) nuts. Highest infection (100%) on bait nuts was also obtained in CAMT x MRD hybrid 3.5 days after inoculation. Reisolation of Phytophthora from bait nuts gave positive results. Morphological characterization of the sporangium showed considerable variation in shapes and size. More Phytophthora propagules was obtained in soil samples collected in areas previously planted with Malayan Yellow Dwarf x West African Tall (MAWA). Phytophthora palmivora is basically a soil borne pathogen but could easily be transported by wind and rainsplash, tent building ants and flying beetles,.